How Well Is Helicobacter pylori Treated in Usual Practice? - Kumaresan Yogeswaran; Grant Chen; Lawrence Cohen; Mary Anne Cooper; Elaine Yong; Eugene Hsieh; Corwyn Rowsell; Fred Saibil; Jill Tinmouth (Canadian Journal of Gastroenterology)
BACKGROUND: Helicobacter pylori is a WHO class I carcinogen also associated with nonmalignant gastrointestinal diseases. Effective treatment exists, and all persons infected with H pylori should receive treatment. However, data regarding the rates of treatment prescription in clinical practice are lacking.